Calcium sulfate-Cu2+ delivery system improves 3D-Printed calcium silicate artificial bone to repair large bone defects - Gao, Shijie; Li, Jiawen; Lei, Qingjian; Chen, Yan; Huang, Huayi; Yan, Feifei; Xiao, Lingfei; Zhang, Tie; Wang, Linlong; Wei, Renxiong; Hu, Chao (Frontiers in Bioengineering and Biotechnology, 2023)
There are still limitations in artificial bone materials used in clinical practice, such as difficulty in repairing large bone defects, the mismatch between the degradation rate and tissue growth, difficulty in vascularization, an inability to address bone defects of various shapes, and risk of infection. To solve these problems, our group designed stereolithography (SLA) 3D-printed calcium silicate artificial bone improved by a calcium sulfate-Cu2+ delivery system. SLA technology endows the scaffold with a three-dimensional tunnel structure to induce cell migration to the center of the bone defect. The calcium sulfate-Cu2+ delivery system was introduced to enhance the osteogenic activity of calcium silicate. Rapid degradation of calcium sulfate (CS) induces early osteogenesis in the three-dimensional tunnel structure. Calcium silicate (CSi) which degrades slowly provides mechanical support and promotes bone formation in bone defect sites for a long time. The gradient degradation of these two components is perfectly matched to the rate of repair in large bone defects. On the other hand, the calcium sulfate delivery system can regularly release Cu2+ in the temporal and spatial dimensions, exerting a long-lasting antimicrobial effect and promoting vascular growth. This powerful 3D-printed calcium silicate artificial bone which has rich osteogenic activity is a promising material for treating large bone defects and has excellent potential for clinical application.